A glance at the use of IRaMuTeQ® software in scientific research: a bibliometric study - Carvalho, Dayara de Nazaré Rosa de; Aguiar, Viviane Ferraz Ferreira de; Apolinário, Daiane Baldo; Bendelaque, Dandara de Fátima Ribeiro; Pereira, Luana Cunha Galvão; Figueira, Simone Aguiar da Silva; Orlandi, Fabiana de Souza (Revista de Enfermagem da UFPI, 2024)
Objective: To analyze and map the national and international scientific production on IRAMuTeQ® use software in scientific research in health in the historical series from 2012 to August 2022. Methods: This is a descriptive bibliometric and scientometric research and exploratory. Collection was carried out in August 2022 through institutional online access to the CAPES Journals Portal, in the Scopus database (Elsevier). To guide the research, the keyword “IRaMuTeQ” was used. After the selection process of included studies, data set was saved in a single file in CSV Excel format and later exported to the VOSviewer® software. Results: It was observed a greater number of articles on the topic in 2021 (127; 34.70%). In Brazil, there is the largest number of authors who publish using IRaMuTeQ® (271; 74.04%). Social sciences and nursing are the two professional areas that most use the software in their articles. Of the 15 authors who most publish with IRaMuTeQ®, 12 are Brazilian. Conclusion: IRaMuTeQ® use assessment in scientific research allows us to point out the expressive role of Brazil in using this tool in scientific research.